1986
DOI: 10.1080/00480169.1986.35343
|View full text |Cite
|
Sign up to set email alerts
|

Equine laryngeal hemiplegia part IV. muscle pathology

Abstract: This study confirmed that neurogenic muscle pathology exists in intrinsic laryngeal muscles supplied by the recurrent laryngeal nerves in horses subclinically and clinically affected with laryngeal hemiplegia. An important additional observation was the occurrence in three out of four laryngeal hemiplegic horses of neurogenic muscle changes in a hindlimb muscle, the extensor digitorum longus, a muscle supplied by another long peripheral nerve. This finding suggests that a polynenropathy exists in laryngeal hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 5 publications
4
51
0
Order By: Relevance
“…A minor, hybrid fiber type with histochemical characteristics of both fast and slow fibers was also present (Gunn 1972;Cahill and Goulden 1986b;Duncan et al 1991a;LopezPlana et al 1993;Adreani et al 2006). The present work on apparently normal laryngeal muscles, using MyHCs as markers, revealed that the fast fibers could be subdivided into two distinct types, 2a and 2x, each with a distinct motor protein and hence speed of contraction.…”
Section: Muscle Fiber Types In the Cad And Tra Of Horses In The Normamentioning
confidence: 99%
See 3 more Smart Citations
“…A minor, hybrid fiber type with histochemical characteristics of both fast and slow fibers was also present (Gunn 1972;Cahill and Goulden 1986b;Duncan et al 1991a;LopezPlana et al 1993;Adreani et al 2006). The present work on apparently normal laryngeal muscles, using MyHCs as markers, revealed that the fast fibers could be subdivided into two distinct types, 2a and 2x, each with a distinct motor protein and hence speed of contraction.…”
Section: Muscle Fiber Types In the Cad And Tra Of Horses In The Normamentioning
confidence: 99%
“…Fiber-type grouping is known to occur commonly in equine laryngeal muscles (Gunn 1972;Cahill and Goulden 1986b). Up to 30% of horses with no laryngoscopic evidence of laryngeal hemiplegia show fiber-type grouping and histological evidence of neurogenic atrophy in those laryngeal muscles innervated by the left recurrent laryngeal nerve.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of subclinical disease, including axonopathy of the recurrent laryngeal nerve and neurogenic atrophy of the intrinsic laryngeal musculature, is present in nearly twice as many horses. 2,5,6,9 The clinical effects of RLN and the histologic changes in the affected laryngeal muscles have been well characterized; [15][16][17]25,33 however, little is known about the cellular and molecular level events that occur in the laryngeal muscle of horses affected by RLN.…”
Section: Introductionmentioning
confidence: 99%